A COMPARATIVE STUDY OF CHANGES IN LIPID PROFILE IN DIFFERENT AGE GROUPS W.S.R. PRAKRITI (International Journal of Ayurveda and Pharma Research, 2015)
The progressive increase in the incidence of hyperlipidaemia and cardiovascular disease in developing countries has led to the rapid development of studies of this condition, particularly its etiopathology. Therefore, the main objective of present research work is to study how lipid profile values vary with Age and Prakriti (constitution) and to suggest life style modifications to combat these variations. Sixty volunteers were taken for clinical trial and were divided into 2 groups and study was conducted in Ayurvedic & Unani Tibbia College and Hospital in 2007-08. It was found that the levels of Cholesterol, Triglycerides, LDL-C and VLDL increased with age and were higher in Kaphapittaja Prakriti. So, life style changes and regular exercise must be done with increasing age and in Kaphapittaja prakriti.